A Knowledge‐Based View of the Porter Hypothesis. (19th June 2013) - Ziesemer, Thomas
ABSTRACT: It is commonly held that environmental regulation affects competitiveness negatively. The Porter Hypothesis contests this view by proposing a dynamic perspective in which innovations induced by apt environmental policies may offset regulation costs. The existing theoretical evidence largely suggests that the classic perception of a trade‐off between economic and ecological goals prevails. Some empirical evidence, however, supports the Porter Hypothesis. With the aim to shed more light on these ambiguities this paper argues that the Porter Hypothesis lacks a comprehensive microeconomic foundation as it does not consider the properties and ramifications of knowledge capital. To address this shortcoming the paper develops a novel knowledge‐based view of the hypothesis that introduces cumulative knowledge capital as the most important asset in attaining a sustainable competitive advantage in the sense of the resource‐based view of the firm. Based on the basic properties of knowledge the new perspective, which is applicable to both incremental and radical innovations, highlights the development and accumulation processes of superior knowledge capital and further discusses the barriers to its growth. In combination with the exogenous pressure of environmental regulation these insights are finally compiled into a knowledge‐based view of the Porter Hypothesis. Copyright © 2013 John Wiley & Sons, Ltd and ERP Environment